MUSIC TOURISM POTENTIALS IN INDONESIA:MUSIC FESTIVALS AND THEIR ROLES IN CITY BRANDING - Hutabarat, Peny Meliaty (UI Scholars Hub, 2022)
The great potential of music tourism has not been optimized in Indonesia. Meanwhile, music tourism is increasingly becoming one of the forms of new economic growth. The growth of music festival from year to year has also made the Indonesian people, especially the younger generation, make music as one of their needs and lifestyles. The number, diversity, and popularity of music festivals in Indonesia have grown tremendously. That’s why Indonesia needs to encourage tourism potentials, one of which is the potential of music festivals that plays a role in creating city image and city branding. This study seeks to see the potential of music tourism and the role of music festivals for city branding. This research is using descriptive methodology seeks to contribute to the development of tourism in Indonesia, by exploring a special interest in tourism, namely music tourism, which is still a new formula in tourism in Indonesia. In addition, it seeks to see the best practices of music festivals in several countries that have succeeded in building the image of the city. Then the DOT-BAS-POS brand and marketing strategy can be used for the creation and development of music tourism in Indonesia. Through this research, it is hoped that the city government, community and society, the tourism sector and universities can work together in the future to encourage and drive music tourism in various tourist destinations in cities in Indonesia by combining natural beauty and music festivals.